2014
DOI: 10.1038/mi.2013.56
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of ovalbumin-induced allergic airway disease following Der p 1 peptide immunotherapy is not associated with induction of IL-35

Abstract: In the present study, we show therapeutic amelioration of established ovalbumin (OVA)-induced allergic airway disease following house dust mite (HDM) peptide therapy. Mice were sensitized and challenged with OVA and HDM protein extract (Dermatophagoides species) to induce dual allergen sensitization and allergic airway disease. Treatment of allergic mice with peptides derived from the major allergen Der p 1 suppressed OVA-induced airway hyperresponsiveness, tissue eosinophilia, and goblet cell hyperplasia upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 64 publications
(101 reference statements)
1
21
1
Order By: Relevance
“…This observation is supported by the results of murine studies in which no increase in the absolute numbers of Foxp3 1 T cells was observed in the lungs of mice after successful peptide therapy (19). On the basis of an assessment of the intensity of Foxp3 staining (20), however, peptide immunotherapy may increase the amount of this regulatory transcription factor per cell, resulting in enhanced suppressive capability. To date, to the best of our knowledge, no functional suppression assays have been performed in the model in question to formally test this hypothesis.…”
Section: Cd25supporting
confidence: 74%
See 3 more Smart Citations
“…This observation is supported by the results of murine studies in which no increase in the absolute numbers of Foxp3 1 T cells was observed in the lungs of mice after successful peptide therapy (19). On the basis of an assessment of the intensity of Foxp3 staining (20), however, peptide immunotherapy may increase the amount of this regulatory transcription factor per cell, resulting in enhanced suppressive capability. To date, to the best of our knowledge, no functional suppression assays have been performed in the model in question to formally test this hypothesis.…”
Section: Cd25supporting
confidence: 74%
“…The functional significance of this increase remains to be determined, as does the role of whole allergen challenge after therapy in the induction of antibody responses in the study by Tarzi and colleagues. In a model of peptide immunotherapy in which mice sensitized to both HDM allergens and OVA were treated with HDM peptides, a significant decrease in the numbers of CD19 1 B cells was observed in lung tissue digests (20). However, no decreases in allergen-specific IgE were observed in the sera of these animals.…”
Section: Modulation Of Humoral Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…In absence of a model allowing to test directly the proliferation of T cell clones in response to HDM Ag, we used a surrogate model (41), in which BMDCs were stimulated with a mixture of HDM and OVA in the presence of CFSE-labeled CD4 + T cells from OVA-TCR transgenic DO11.10/ Rag2 2/2 for 4-9 d. As expected, T cells strongly proliferated, as evidenced by the decreased CFSE signal 4 d after coculture. C5aR1 2/2 BMDCs were equally potent in driving CD4 + T cell proliferation (Fig.…”
Section: In Vitro Proliferation and Differentiation Of Th Cells Are Imentioning
confidence: 99%